Abdominal fat sub-depots and energy expenditure: Magnetic resonance imaging study. Issue 3 (June 2017) - Serfaty, Dana; Rein, Michal; Schwarzfuchs, Dan; Shelef, Ilan; Gepner, Yftach; Bril, Nitzan; Cohen, Noa; Shemesh, Elad; Sarusi, Benjamin; Kovsan, Julia; Kenigsbuch, Shira; Chassidim, Yoash; et al.
Summary: Background & aims: We aimed to assess the association between the distinct abdominal sub-depots and resting energy expenditure (REE). Methods: We performed magnetic resonance imaging (MRI) to quantify abdominal visceral-adipose-tissue (VAT), deep-subcutaneous-adipose-tissue (deep-SAT), and superficial-subcutaneous-adipose-tissue (superficial-SAT). We measured REE by indirect-calorimetry. Non-exercise activity thermogenesis (NEAT) [1–3 metabolic equivalents (METs)] and exercise thermogenesis (activities of 4+METS ) were estimated based on 6-days of accelerometry to assess total physical activity energy expenditure (PAEE). Results: We studied 282 participants: 249 men [mean age = 47.4 years, body-mass-index (BMI) = 31 kg/m 2, mean VAT proportion from total abdominal fat = 34.5%, mean superficial-SAT proportion from total abdominal fat = 24.3%] and 33 women (mean age = 51.2 years, BMI = 30.1 kg/m 2, mean VAT proportion from total abdominal fat = 22.8%, mean superficial-SAT proportion from total abdominal fat = 37.8%). As expected, women had lower REE [by 32.4% (1488 ± 234 kcal/day vs. 1971 ± 257 kcal/day; p < 0.01)] and lower REE/kg [by 8% (19.6 ± 3 kcal/kg vs. 21.2 ± 2 kcal/kg; p < 0.01)] than men. Exercise and total PAEE were positively associated with REE/kg (p < 0.01 for both) and a positive correlation between NEAT and REE/kg was borderline (p = 0.056). Participants, in whom abdominal VAT was the dominant proportional depot, had higher REE (1964 ± 297 kcal/day vs. 1654 ± 352 kcal/day; p < 0.01) and higher REE∖kg (22.2 ± 2.3 kcal/kg/day vs. 19.6 ± 2.5 kcal/kg/day; p < 0.01) than participants in whom superficial-SAT was the largest proportional depot. In multivariate models, adjusted for age, gender and residual BMI, increased VAT proportion was independently associated with higher REE (β = 0.181; p = 0.05). Likewise, increased VAT proportion (β = 0.482; p < 0.01) remained independently associated with higher REE/kg. In this model younger age (β = −0.329; p < 0.01) was associated with higher REE/kg. Conclusions: Abdominal fat distribution patterns are associated with varying levels of resting energy expenditure, potentially reflecting different metabolic rates of adipose sub-depots and providing an anatomic/anthropometric link to physiological obese sub-phenotypes.